NUTRIENT DIGESTIBILITY AND HAEMATOLOGY OF YANKASA SHEEP FED DIFFERENT LEVELS OF AFRICAN BIRCH (Anogeissus leiocarpus) LEAVES AND WHEAT OFFALS - Dumbari, M. K.; Abdullahi, H. J.; Abubakar, M.; Yerima, J.; Muhammad, A. S. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study was conducted to investigate nutrient digestibility and haemato-biochemical indices of twenty (20) growing Yankasa sheep fed varying levels of African birch (Anogeissus leiocarpus) and wheat offals. Four diets (16% CP) were formulated using varying levels of African birch (Anogeissus leiocarpus) leaves at 0, 10, 20 and 30% in the diets and termed as diets 1, 2, 3 and 4 respectively. Each treatment diet was randomly allotted with five randomly selected animals each and laid in a Completely Randomized Design. The experiments lasted for 12 weeks and the 11th week, the nutrient digestibility and blood haematology were determined. For nutrient digestibility, the total feed intake and the faeces voided obtained and percentage of their relationship was determined. For haematology and biochemical studies, 5 ml of blood samples were collected via jugular vein of randomly sampled rams, stored and transported in refrigerated condition to laboratory for analysis. DMD of diet 1 (86.69%) was statistically (P<0.05) superior to diets 2, 3 and 4 (85.11, 82.05% and 79.4%). All the haematological and biochemical values obtained for all parameters across the treatments were statistically (P<0.05) similar and fell within the normal range values for healthy rams. Based on these findings, diet 1 could be recommended to be fed to Yankasa sheep for optimum utilization.